Performance Based Skills Gap Analysis in Tanzanian Small Scale Manufacturing Firms - Galan Mashenene; Gordian Bwemelo; Evelyne Magambo; Alfred Sallwa (International Journal of Management, Accounting and Economics)
The performance of small firms, particularly those engaged in small-scale manufacturing, is a critical issue not only in Tanzania but throughout the world. This study analyzed the skills gap and how it affects the performance of small-scale manufacturing sector in Mwanza and Dar es Salaam cities in Tanzania. Gathering of quantitative data was performed under usage of a standardized questionnaire from 175 randomly selected small-business owner and employed managers. The analysis of data was aided using tools for analysis known as Statistical Package for Social Sciences (SPSS) and Ms. Excel whereas descriptive statistics in form of percent, frequence and means scores were computed. Further, crosstab to establish how variables are associated was achieved by performing Chi-Square.  Skills gaps were established by taking the difference of mean scores between employers’ perceptions (P) and expectations (E). Determination of skills gap on SSMFs’ performance was achieved using Logit model. The findings indicated that the skills gap exists with an overall mean score of -0.7302. The findings further exhibited that skills gaps including technical, communication, problem solving, interpersonal and decision making statistically were significant with negative relationships (p < 0.05). The recommendations made include policymakers, development partners and owners of SSMFs to collaborate in closing identified skills gaps by designing training programmes with sufficient budgets being set aside for the training sessions.